2012
DOI: 10.1159/000341462
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA Improves miR-133 Expression Through MAPK ERK1/2 Pathway in Hypoxic Cardiac Myocytes

Abstract: Tanshinone IIA is a lipid-soluble pharmacologically active compound extracted from the rhizome of Chinese herb Salvia miltiorrhiza, a well-known traditional Chinese medicine used for the treatment of cardiovascular disorders. Previous studies have identified that tanshinone IIA inhibited overexpression of miR-1 in hypoxic neonatal cardiomyocytes. This study was designed to examine the effects of tanshinone IIA on miR-133 expression under hypoxic condition. Neonatal rat cardiomyocytes were cultured in a hypoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 35 publications
(43 reference statements)
1
31
0
Order By: Relevance
“…The relative expression of miR-133 was calculated and normalized to U6 using the comparative Cq method. Relative expression intensity values were calculated as 2 -ΔΔCq (16). The RT-qPCR was performed using the SYBR green method with an Applied Biosystems 7500 Real-Time PCR System (Thermo Fisher Scientific, Inc.).…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative expression of miR-133 was calculated and normalized to U6 using the comparative Cq method. Relative expression intensity values were calculated as 2 -ΔΔCq (16). The RT-qPCR was performed using the SYBR green method with an Applied Biosystems 7500 Real-Time PCR System (Thermo Fisher Scientific, Inc.).…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…Due to their involvement in the regulation of gene expression, miRNAs serve an important role in cardiac function, including the conductance of electrical signals, heart muscle contraction, development and morphogenesis; miRNAs are also involved in the proliferation and apoptosis of cardiomyocytes, cardiac hypertrophy and heart failure (13)(14)(15). In particular, a number of studies suggest that miRNA-133 (miR-133) serves an important role in the cardiovascular system (15)(16)(17). In the present study, the role of miR-133 in the myocardial protective effect of tanshinone IIA against hydrogen peroxide (H 2 O 2 )-induced induce cell death was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidences show that miRNAs play pivotal roles in diverse aspects of heart diseases, including myocardial ischemia [10,11], apoptosis [12,13], arrhythmia [14], cardiac fibrosis [15], and heart failure [16,17]. Notably, evidence from recent studies has shown that miRNAs are involved in regulating cardiomyocyte cell size, cardiac growth and fibrosis in cardiac hypertrophy [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…These results also suggest an anti-apoptotic function of miR-133. 25 Accordingly, the compound loss of both copies of miR-133a in mice (miR-133a-1 and miR-133a-2) resulted in enhanced apoptosis. 9,26 Finally, we observed a decreasing proliferation index with increasing gestational age, as measured by the expression of Ki67, where proliferation rates remained high until the 25 th gestational week, but decreased significantly after the 29 th gestational week.…”
Section: Discussionmentioning
confidence: 99%